PENGARUH INVESTASI, PENGELUARAN PEMERINTAH, TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN TINGKAT KEMISKINAN PADA WILAYAH SARBAGITA DI PROVINSI BALI - Ratih, G.A. Pt. Ambara; Utama, Made Suyana; Yasa, I NYoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
Poverty is one of the fundamental problems in any country. Poverty is not only experienced by the developing countries, but also for developed countries including Indonesia, especially in the Region of Sarbagita in the Province of Bali. The decline in the poverty rate could be seen through from Gross Domestic Regional  Product (GDRP). GDRP dependent on the realization of investments Investment, Government Expenditure and Labor. The high Investment and Government Expenditure on Region of Sarbagita will increase Gross Domestic Regional  Product (GDRP) and influenced to the public welfare and will further reduce the level of poverty.
Keywords: Investment, Government Expenditure, Labor, Gross Domestic Regional Product ( GDRP) and Poverty Level